2022
DOI: 10.1007/s12035-022-02753-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential Brain and Cerebrospinal Fluid Proteomic Responses to Acute Prenatal Endotoxin Exposure

Abstract: BackgroundChorioamnionitis (CA) is a risk factor for preterm birth and is associated with neurodevelopmental delay and cognitive disorders. Prenatal in ammation-induced brain injury may resolve during the immediate postnatal period, which is a time of rapid metabolic and brain remodeling. Cerebrospinal uid (CSF) collected at birth may be a critical source of predictive biomarkers. Using pigs as a model of preterm infants exposed to CA, we hypothesized that prenatal lipopolysaccharide (LPS) exposure induces pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Among the 23 genes previous studies have shown their correlation with AD, we have: GFAP [ 41 , 42 ], PDGFRβ [ 43 45 ], NFKBIA [ 46 ], TNFRSF1B [ 47 ], NOTCH1 [ 48 ], BCL6 [ 49 ], CSF1R [ 50 ], LEP [ 51 ], DCLRE1C [ 52 ], KCNJ10 [ 53 ], MAP2K1 [ 54 ], VIP [ 55 ], SNCA [ 56 ], ENO2 [ 57 ], SST [ 58 ], UCHL1 [ 59 ], HPRT1 [ 60 ], STAT4 [ 61 ], CD14 [ 62 ], ITGB2 [ 63 ], SPP1 [ 64 ], STX1A [ 65 ], and SYP [ 66 ]. And these genes are involved in the regulation of molecules associated with the complement system, for instance, GFAP [ 67 ], PDGFRβ [ 68 ], NFKBIA [ 69 ], TNFRSF1B [ 70 ], NOTCH1 [ 71 ], BCL6 [ 72 ], CSF1R [ 73 ], LEP [ 74 ], DCLRE1C [ 75 ], KCNJ10 [ 76 ], MAP2K1 [ 77 ], VIP [ 78 ], SNCA [ 79 ], ENO2 [ 80 ], SST [ 81 ], UCHL1 [ 82 ], HPRT1 [ 83 ], STAT4 [ 84 ], CD14 [ 85 ], ITGB2 [ 86 ], SPP1 [ 87 ], STX1A [ 88 ], and SYP [ 89 ]. However, few studies have discussed their role in AD pathology by modulating the complement system, our study may be a new perspective for our future exploration of the relationship between AD and the complement system.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 23 genes previous studies have shown their correlation with AD, we have: GFAP [ 41 , 42 ], PDGFRβ [ 43 45 ], NFKBIA [ 46 ], TNFRSF1B [ 47 ], NOTCH1 [ 48 ], BCL6 [ 49 ], CSF1R [ 50 ], LEP [ 51 ], DCLRE1C [ 52 ], KCNJ10 [ 53 ], MAP2K1 [ 54 ], VIP [ 55 ], SNCA [ 56 ], ENO2 [ 57 ], SST [ 58 ], UCHL1 [ 59 ], HPRT1 [ 60 ], STAT4 [ 61 ], CD14 [ 62 ], ITGB2 [ 63 ], SPP1 [ 64 ], STX1A [ 65 ], and SYP [ 66 ]. And these genes are involved in the regulation of molecules associated with the complement system, for instance, GFAP [ 67 ], PDGFRβ [ 68 ], NFKBIA [ 69 ], TNFRSF1B [ 70 ], NOTCH1 [ 71 ], BCL6 [ 72 ], CSF1R [ 73 ], LEP [ 74 ], DCLRE1C [ 75 ], KCNJ10 [ 76 ], MAP2K1 [ 77 ], VIP [ 78 ], SNCA [ 79 ], ENO2 [ 80 ], SST [ 81 ], UCHL1 [ 82 ], HPRT1 [ 83 ], STAT4 [ 84 ], CD14 [ 85 ], ITGB2 [ 86 ], SPP1 [ 87 ], STX1A [ 88 ], and SYP [ 89 ]. However, few studies have discussed their role in AD pathology by modulating the complement system, our study may be a new perspective for our future exploration of the relationship between AD and the complement system.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, decreased levels of EPHA4 may facilitate an anti-inflammatory microglia phenotype, since EphA4 deletion inhibits microglia proliferation and promotes the M2 polarization (Wei et al, 2019 ). Preclinical studies in pigs showed that the microglial response to inflammatory challenges is transient (Muk et al, 2022 ), however the early-life immune activation makes this long-living tissue resident macrophages more sensitive to a secondary inflammatory insult later in life, and may also have long-term behavior impact (Bilbo et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently the Pankratova Lab published a study investigating the exposure of porcine fetuses to intra-amniotic injection of 1 mg liposaccharide (LPS), which can cause intrauterine inflammation at embryonic gestation day 103 (E103) prior to cesarean section delivery at E106 [ 115 ]. They analyzed GFAP immunoreactivity in the cortex, hippocampus, and periventricular white matter at day 1 (P1) and day 5 (P5) after birth.…”
Section: Previous Investigations Of Porcine Astrocytes In Neurotrauma...mentioning
confidence: 99%